A new species of Parapsestis Warren, 1912 (Lepidoptera, Drepanidae, Thyatirinae) from Yunnan, China with a key to species of the genus - Deng, Zhongwei; Qiao, Chuhang; Liu, Yingqi; Han, Huilin; Zhang, Aibing (Zootaxa, 2026)
A new species of the genus Parapsestis Warren, 1912, P. atramentaria Deng, Liu & Han sp. nov., is described from Yunnan Province, China. The illustrations of the male habitus and genitalia of the new species and its most similar species, P. lichenea (Hampson, [1893]), are provided, together with the habitus of another five species that are also distributed in Yunnan Province. A key to all species of Parapsestis is provided, along with a morphological comparison of the new species and its related species.